Prevalence of adverse reactions to intravenously administered originator biologics in patients with rheumatoid arthritis: A 5-year retrospective study - Haya M. Almalag; Shiekha S. Alaujan; Hawazin S. Alhazzani; Lamia A. Alzamel; Reem S. Tashkandi; Hussain F. Alarfaj; Abdurhman S. Alarfaj; Mohammed A. Omair (Elsevier, 2022)
Background: Few Saudi studies have examined adverse drug reactions (ADRs) in patients with rheumatoid arthritis (RA) receiving intravenous (IV) originator biologics. Therefore, this study aimed to evaluate the prevalence, types, and predictors of ADRs following long-term IV originator biologic use in patients with RA. Patients and methods: This retrospective, single-center study included adult patients with RA who received IV originator biologics between 2015 and 2020. Medical records were reviewed and data regarding ADRs were collected and evaluated for causality using the Naranjo scale. Binary logistic regression analysis was performed to identify the odds for and factors associated with developing ADRs for each biologic. Results: A total of 129 patients (87.6% women) with a mean (standard deviation) age of 54 (13) years were included in this study. A total of 1963 doses of tocilizumab (38.76%), rituximab (38.76%), abatacept (13.95%), and infliximab (8.53%), were administered during the study period. ADRs with a Naranjo score ≥ 1 were experienced by 103 (78%) patients, with an average of 2.2 events per patient. Infection (26.6%) and skin and mucous membrane disorders (14.18%) were the most commonly reported ADRs. Abatacept was associated with a significantly higher risk of multiple ADRs than the other biologics (adjusted odds ratio: 3.145, 95% confidence interval 1.004-9.854, p = 0.049). Conclusion: There was a high prevalence of ADRs among patients with RA receiving biologics. Abatacept was associated with a greater risk of multiple ADRs than other biologics. Infection was the most common ADR. Future multicenter longitudinal studies are warranted.